Lead in Breast Milk of Nursing Mothers Working in Agricultural Farms - Muhammad Abdul Raziq, Maria Gill, Attiqa Khalid, Misbah-Ul-Qamar, Hina Sadaf, Zobiah Hafeez, Maria Aslam, Tehseen Iqbal, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To detect lead in breast milk of mothers working in agricultural farms adjacent to Bahawalpur, Pakistan. Study design: Descriptive study Methods: This study was conducted in the Physiology and cell biology department of, University of Health Sciences (UHS), Lahore after obtaining consent from ethical review board of UHS, Lahore. Total 91 lactating female farm workers were selected for this study who had been working in the farm for one year in last three years. Five to six ml of breast milk was obtained from each lady. Samples underwent the process of dry digestion at 500°C for 4 hours. White ash obtained was mixed with deionized solution and inductively coupled plasma spectroscopy was used to detect the lead levels in milk samples of nursing mothers Results: Out of 91 samples, lead levels were detected in 42 samples (46.15%). The mean (mean±SD) values of milk lead (n=42) were 781.49±1034.33µg/l. Family history of intellectual disability was significantly associated with milk concentrations of lead (p = 0.046). Conclusion: Present study concludes that the level of milk lead is found to be considerably higher in nursing mothers working in agricultural farms as compared with the levels reported by others from different countries. Key words: Inductively coupled plasma spectroscopy, lead, breast milk, graphite Furnace Atomic Absorption Spectrometry technique